IDENTITAS KEINDONESIAAN DALAM NOVEL KARYA ANAK INDONESIA - Suyatno Suyatno (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to describe Indonesian identities in novels by Indonesian children.The data sources were 11 randomly selected Indonesian child novels. The data comprisedIndonesian information in novel narration. The data were collected through reading andnoting techniques. They were analyzed using the thematic analysis technique through thesteps of: describing the structure, interpreting the structure, giving thematic meanings,drawing thematic conclusions, and relating themes to other aspects. The findings areas follows. First, Indonesian identities include aspects of nationalism and statehood.The former is characterized by the use of the Indonesian language, batik art, traditionalgames, shadow puppet art, Javanese and Sundanese traditions, nationalism, and socialaffairs. The latter includes: Pancasila, the Indonesian language, Indonesian state, cities inIndonesia, and the red and white flag. Second, Indonesian identities in novels by childrenare developed through dialogues, narration, and description.